Transformation in Central European Postsocialist Cities - Enyedi, György (Discussion Papers, 1998)
Cities have traditionally been the agents and co-ordinators, as well as the subjects of the societal changes that have effected their transformation. An analysis of urban transformation may contribute to a more fundamental understanding of societal changes. However, few of the countless studies on the postcommunist transition discuss the development of cities. Although there has been considerable attention given to selected topics, comprehensive and authoritative studies are lacking. The present work aims to provide precisely such a comprehensive description of urban transition. In the first part of the study, the author briefly summarises the characteristics of the urban system in state-planned economy in order to clarify the main consequences of the transition, and make it easier to assess the chances of European integration. In the second, main section of the study, key factors of the transition process are analysed, (the new integration of the settlement system, the transformation of the urban economy, the establishment of local governments, the evolution of the real estate market, the transformation of urban society and of the built environment and the international relations and participation in the international competition of cities). Finally, the author weighs the prospects of a new united European urban system in the third, concluding part.